Effect of fish density during transportation on stress and mortality of juvenile Tambaqui Colossoma macropomum - Gomes, Levy C.; Araujo-Lima, Carlos A. R. M.; Roubach, Rodrigo; Chippari-Gomes, Adriana R.; Lopes, Nívia P.; Urbinati, Elisabeth C. [UNESP] (My University, 2003)
The increased demand for juvenile tambaqui Colossoma macropomum for grow-out ponds and stocking programs in the Amazon state of Brazil has increased the transportation of this species. This study was designed to determine the optimum density of juvenile tambaqui during transportation in closed containers. Fish (51.9 ± 3.3 g and 14.9 ± 0.4 cm) were packed in sealed plastic bags and transported for 10 h at four densities: 78, 156, 234, and 312 kg/m3. After transportation, fish from each density were kept in separate 500-L tanks for 96 h. Mortality, 96-h cumulative mortality, water quality, and blood parameters (hematocrit, plasma cortisol, and glucose) were monitored. Fish mortality after transportation was significantly lower at densities of 78 and 156 kg/m3 than at 234 and 312 kg/m3. Cumulative mortality was significantly lower at a density of 78 kg/m3. Dissolved oxygen after 10 h of transportation remained high at a density of 78 kg/m3, but reached critically low values at all other densities. Ammonia concentration was highest at the lowest density and was lower at higher densities. Carbon dioxide concentration was lowest at the density of 78 kg/m3 but higher in the other treatments. Plasma glucose and cortisol increased significantly immediately after transportation at densities of 156, 234, and 312 kg/m3, returning to control values by 24 h. The best density for juvenile tambaqui during a 10-h transportation haul in a closed container was 78 kg/m3. At this density there was no fish mortality, water quality was kept within acceptable values, and fish were not stressed.
Keywords: fish culture; Colossoma macropomum